Estudio factibilidad para la creación de un centro de acopio para la comercializaciónde maracuya, en el cantón Buena Fe, provinciade los Rios, año 2014 - Bravo Loor, Ibis Johana (2015)
The present research intends to conduct a feasibility study for building a collection center for the marketing of fruit in the Canton Buena Fe, Los Rios Province. According to data from the Survey of Surface and continuous production (SPACE) of the National Institute of Statistics and Census (INEC), the province of Los Rios, is characterized as one of the provinces with the highest concentration of plantations and production of passion fruit nationwide in 2014 our country has an area planted with 12,500 (Has), which give a production of 135,000 tonnes per year, in the province of Los Rios contributes with 70% of total production, placing it as the third most domestic production. According to the results of research shows that the project is viable considering the willingness of producers in the sector to market your product in the new distribution center, the area also has a considerable volume production to supply the center. The study has projected five years, where the financial resources required for the implementation of the business amounted to $ 449,154.77, of which 26.72% is equity capital and 73.28%, it will manage with the National Finance….